MEDICAL IMPORTANCE OF AK PLANT (CALOTROPIS PROCERA) IN TREATMENT OF HUMAN DISEASES (Journal of Medical & Health Sciences Review, 2025)
From ancient times to the present, herbal remedies have been used. The history of ethnopharmacology predates humankind. Herbal remedies have an astounding range of therapeutic applications. Ayurvedic plants like Calotropis procera Linn. are utilized in many traditional medicines to treat a wide range of ailments. There is substantial medicinal efficacy in the plant's extracts from various sections. When dried, the entire plant has strong expectorant, antihelmintic, and tonic properties. The roots function similarly and have laxative properties as well. The latex is traditionally used to cure vertigo, baldness, hair loss, toothache, intermittent fevers, rheumatoid/joint swellings, and paralysis, while the powdered root is used to treat bronchitis, asthma, leprosy, dermatitis, and elephantiasis. It is used to alleviate joint pain with the leaves.